THE LEAN HOSPITAL APPROACH TO CONTINUOUS IMPROVEMENT IN ENHANCING SERVICE QUALITY AT THE OUTPATIENT PHARMACY OF TALAUD REGIONAL GENERAL HOSPITAL IN 2019 - Meyvie Belinda Kendage; Jason Merari Peranginangin; Tri Wijayanti (RADJA PUBLIKA, 2025)
The pharmacy is one of the medical support facilities in hospitals. However, there are still many problems encountered in its services that reduce patient satisfaction, such as inefficient room layout, inadequate drug supplies, and suboptimal service times. The purpose of this study is to identify critical waste and the root causes of critical waste in the process of serving outpatients at the Talaud Regional General Hospital Pharmacy. The method used in this study is a case study with a qualitative and quantitative approach. The stages of the study are observation of the service process flow, distribution of value and waste questionnaires, and interviews. The results of the value stream mapping obtained from the prescription dispensing service process showed a lead time of 24.89 minutes and a VAR of 63% for general patients, a lead time of 18.45 minutes and a VAR of 67% for BPJS patients, and a lead time of 14.72 minutes for non-dispensing prescriptions. VAR of 51% for general patients, and a lead time of 11.61 minutes and VAR of 56% for BPJS patients. The critical waste identified was transportation waste at 20.2%. The root causes of transportation waste were the distant layout of the rooms, the prescribed drugs not being available at the pharmacy, and the doctors' requests not matching those of the pharmacy.